PELATIHAN PEMBUATAN WEBSITE SEDERHANA SEBAGAI UPAYA PENINGKATAN KOMPETENSI DIGITAL UNTUK SISWA SMP NEGERI 14 DEPOK - Angga Suryadi; Nasrul Hidayah; Eko Sutono (Abdi Jurnal Publikasi, 2024)
The web is a collection of several integrated pages aimed at conveying information to web URL accessors, available individually, to communities/groups, or organizations. A Web Developer is a programmer who specializes in developing web applications (World Wide Web) and is fully involved in developing web applications by building applications based on the Client-Server Model. SMPN 14 Depok was established as part of the government's efforts to provide access to secondary education for the people of Depok and its surroundings. The establishment of this school may have started since the formation of Depok city in 1982. With the increasing population and the need for educational facilities, SMPN 14 Depok was established as one of the secondary education institutions in the area. Therefore, we, lecturers from Pamulang University, wish to conduct community service (PKM) at SMPN 14 Depok. The method used in this PKM includes training and lectures. The Simple Website Creation Training as an Effort to Improve Digital Competence for SMPN 14 Depok Students is an initiative aimed at providing basic understanding and skills to students in creating websites. By introducing simple website creation training, it is hoped that students can develop a better understanding of the basic concepts of web technology and acquire practical skills relevant to current and future needs. Furthermore, improving digital competence is also considered to have a positive impact in preparing students for various career fields that require an understanding of information technology.